Obeticholic Acid Induces Hepatoxicity Via FXR in the NAFLD Mice - Lin, Chuangzhen; Yu, Bingqing; Chen, Lixin; Zhang, Zhaohui; Ye, Weixiang; Zhong, Hui; Bai, Wenke; Yang, Yuping; Nie, Biao (Frontiers in Pharmacology, 2022)
Objective: Obeticholic acid (OCA), a potent farnesoid X receptor (FXR) agonist, is a promising drug for nonalcoholic fatty liver disease (NAFLD); however, it can cause liver injury, especially at high doses. Here, we investigated the role of FXR in the high-dose OCA-induced hepatoxicity in the condition of the NAFLD mouse model. Methods: Wild-type (WT) mice and FXR-/- mice were administered with over-dose OCA (0.40%) and high-dose OCA (0.16%), in a high-fat diet. RNA-seq on liver samples of mice fed with high-dose OCA was performed to dig out the prominent biological events contributing to hepatic fibrosis. Results: Over-dose OCA induced liver injury and shortened survival in WT mice, but not FXR-/- mice. High-dose OCA caused hepatic stellate cell activation and liver fibrosis in the presence of FXR. Furthermore, high-dose OCA induced cholesterol accumulation in livers via the upregulation of genes involved in cholesterol acquisition and downregulation of genes regulating cholesterol degradation in liver, leading to the production of interleukin -1β and an FXR-mediated inflammatory response. Conclusions: The high-dose OCA induced FXR-dependent hepatic injury via cholesterol accumulation and interleukin -1β pathway in the NAFLD mice.